Habilidades para a vida na melhoria da convivência familiar de adolescentes em situação de distanciamento social devido à pandemia da COVID-19 - Santos, Edna Messias de Freitas (2022)
In the context of the pandemic caused by the spreading of the new coronavirus (SarsCoV-2), social distancing measures have been adopted throughout the national territory. Social distancing may present challenges in the way people relate to each other, as it increases home-based environment family life and decreases coexistence with other people and contexts, involving changes in the daily routine of work, study, leisure, etc. This context can be more difficult for adolescents because, in general, they seek to develop a greater autonomy, independence and live closer to the peer group at this stage of life. Thus, difficulties in family relationships, conflicts and situations of violence may increase in social distancing. In this context, the life skills proposed by the World Health Organization, such as effective communication, problem and conflict solving, dealing with feelings and emotions, empathy, among others, could be a positive resource for adolescents. Because of that, the goal of this study was to identify adolescents' perceptions of their life skills and family life during the period of social distancing due to the COVID-19 pandemic. This is qualitative research carried out with eight adolescents, of both genders, aged between 12 and 14 years old, who have been selected in a non-probabilistic way, for convenience. They have been chosen by means of the technique known as snowball sampling, in which an initial participant indicates another one and so on. Data have been collected through semi-structured interviews and analyzed by Content Analysis. The results showed the quality and aspects which hinder the adolescents' family relationships during social distancing, as well as the proposals suggested by the adolescents to reduce the difficulties identified. They have also presented the life skills they used during the period of social distancing, highlighting the importance of such skills in family life. It is concluded that it is important to investigate life skills in adolescence, especially in the context of social distancing, because they enable people to deal effectively with the demands, challenges and conflicts of everyday life, providing well-being. This perspective is in line with the seventh objective of the National Health Promotion Policy, which aims to promote empowerment, decision-making processes and the development of greater autonomy for people and communities through the development of personal skills. Keywords: Adolescents. COVID-19. Social distancing. Life skills.